Effects of the gut microbiota and its metabolite short-chain fatty acids on endometriosis - Liu, Menghe; Peng, Ru; Tian, Chunfang; Shi, Jianping; Ma, Jiannan; Shi, Ruiwen; Qi, Xiao; Zhao, Rongwei; Guan, Haibin (Frontiers in Cellular and Infection Microbiology, 2024)
In recent years, a growing body of research has confirmed that the gut microbiota plays a major role in the maintenance of human health and disease. A gut microbiota imbalance can lead to the development of many diseases, such as pregnancy complications, adverse pregnancy outcomes, polycystic ovary syndrome, endometriosis, and cancer. Short-chain fatty acids are metabolites of specific intestinal bacteria and are crucial for maintaining intestinal homeostasis and regulating metabolism and immunity. Endometriosis is the result of cell proliferation, escape from immune surveillance, and invasive metastasis. There is a strong correlation between the anti-proliferative and anti-inflammatory effects of short-chain fatty acids produced by gut microbes and the development of endometriosis. Given that the mechanism of action of gut microbiota and Short-chain fatty acids in endometriosis remain unclear, this paper aims to provide a comprehensive review of the complex interactions between intestinal flora, short-chain fatty acids and endometriosis. In addition, we explored potential microbial-based treatment strategies for endometriosis, providing new insights into the future development of diagnostic tests and prevention and treatment methods for endometriosis.